The role of digital health for post-surgery care of older patients with hip fracture: A scoping review. (April 2022) - Zhang, Jing; Yang, Minghui; Ge, Yufeng; Ivers, Rebecca; Webster, Ruth; Tian, Maoyi
Highlights: The utility of digital health should be expanded to more users and capabilities of interventions, facilitating the care delivery of hip fracture patients after surgery. More research should be designed to explore the role of digital health to mitigate the health system challenges during older hip fracture patient post-surgery care delivery. More research should be developed and implemented to reduce the health service delivery inequity among older hip fracture patietns in resource-constrained settings. There is a need for high-quality large-scale studies with robust design to improve the evidence base. Abstract: Background: Digital health interventions can potentially improve the integration of the health care systems. Hip fracture is a serious injury for older people and integrated post-surgery care is vital for good recovery. Objective: We aimed to characterise digital health interventions used for hip fracture post-surgery care, and further to examine the extent to which of these interventions address the World Health Organisation (WHO) integrated care for older people (ICOPE) framework. Methods: A scoping review was conducted, by searching the literature from English and Chinese databases and trial registries. Keywords included hip fracture, post-surgery care and digital health interventions. Interventional, observational, qualitative studies and case reports were included. We used a combined framework, WHO ICOPE and WHO digital health intervention classifications, to support data synthesis. Results: A total of 4, 542 articles were identified, of which 39 studies were included in the analysis. We identified only six randomised controlled trials. Digital health interventions were mainly used to help doctors provide clinical care and facilitate service delivery between the patients and healthcare providers. No studies focused on health workforce, financial policy or the development of infrastructure. The primary users were healthcare providers and patients, without healthcare managers or the use of data services. Most digital health interventions focused on physical therapy, bone protection and falls prevention. Limited interventions were implemented in low-and middle-income countries. Conclusion: A stronger evidence base is needed to expand the use of digital health for post-surgery care of hip fracture patients, including high-quality larger-scale studies, more focus in resource-constrained settings, expanding to more users and capabilities of interventions, and exploring the role of digital health for the integrated care model to mitigate health system challenges.